SOCIOLOGY OF EDUCATION IN CHARACTER BUILDING - Hirtsul Arifin (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
The results of this study are able to provide answers to what researchers convey that in the science of sociology will be studied various things that can support the implementation of character education, among others, is about the process of socialization, which is one of the important factors to shape and build the nation's character in society. In addition, sociology is also one of the social science groups which will certainly learn about the values and norms, people's behavior, social deviations to social control. Seen from what is learned in sociology are some of the main things that are very influential in shaping the character of society. The research method used is literature, where all the data that can be collected is then analyzed and presented from various data supplementary documents to provide conclusions and a study. The data used were obtained from documents in the form of books, literature relating to this research